Pengembalian Kerugian Keuangan Negara dari Pembayaran Uang Pengganti Tindak Pidana Korupsi, Dapatkah Optimal? (Return of State Financial Losses from The Payment of Substitute Money Corruption Criminal Act, Can It Be Optimal?) - Puteri Hikmawati (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2019)
In addition to being subject to principle criminal penalties, the defendant in a corruption case may be subject to additional criminal penalty, in the form of payment of replacement money. The article which resulting of the normative juridical research with this qualitative approach, review regarding the return of the state financial losses shall be paid from the payment of substitute money in corruption criminal act can it be optimal? In the discussion, the penalty payment of substitute money has been stipulated in Law No. 31 of 1999 on the Eradication of Corruption Crime as amended by Law No. 20 of 2001. The amount of payment of substitute money shall be if possible equal with the assets obtained from the criminal act of corruption. If the substitute money is not paid, then the convicted person shall be liable to a prison sentence whose duration does not exceed the maximum sentence of the principal sentence. Therefore, the returning of financial losses cannot be optimal. The amount of compensation state finances needs to be increased, by confiscating and seizing the assets/properties of the perpetrator. The law concerning assets deprivation shall be established as the legal basis for assets seizure resulting from corruption. AbstrakSelain dapat dijatuhi pidana pokok, terdakwa dalam perkara korupsi dapat dijatuhi pidana tambahan, berupa pembayaran uang pengganti. Artikel yang merupakan hasil penelitian yuridis normatif dengan pendekatan kualitatif ini, mengkaji pengembalian kerugian keuangan negara dari pembayaran uang pengganti dalam tindak pidana korupsi dapatkah optimal?. Dalam pembahasan, pidana pembayaran uang pengganti telah diatur dalam UU No. 31 Tahun 1999 tentang Pemberantasan Tindak Pidana Korupsi sebagaimana telah diubah dengan UU No. 20 Tahun 2001. Jumlah pembayaran uang pengganti sebanyak-banyaknya sama dengan harta benda yang diperoleh dari tindak pidana korupsi. Apabila uang pengganti tidak dibayar, maka terpidana dipidana dengan pidana penjara yang lamanya tidak melebihi ancaman maksimum dari pidana pokoknya. Oleh karena itu, pengembalian kerugian keuangan negara tidak dapat optimal. Jumlah pengganti kerugian keuangan negara perlu ditingkatkan, dengan melakukan penyitaan dan perampasan terhadap aset/harta kekayaan pelaku. UU Perampasan Aset perlu dibentuk sebagai dasar hukum perampasan aset dari hasil korupsi.